Diversity Combining Type I-Hybrid ARQ protocol over m-ary Asymmetric Varshamov channels. (July 2019) - Elmougy, Samir; Pezza, Laura; Tallini, Luca G.; Al-Dhelaan, Abdullah; Bose, Bella
Abstract: Errors in multilevel flash memories and multilevel optical systems are asymmetric in nature because of the underlying device physics. These errors can be modeled using the m -ary asymmetric channel. In this work, a general m ( ≥ 2)-ary Asymmetric Varshamov (AV) channel for these systems is introduced. Also, a Divesting Combining Type-I Hybrid ARQ protocol using t -Asymmetric Error Correcting/All Asymmetric Error Detecting ( t -AEC/AAED) codes is presented and its throughput performance is studied.